Climate-smart agriculture: in need of a theory of scaling - Vernooy, Ronnie; Bouroncle, Claudia (2019)
Since 2011, the CGIAR program on Climate Change, Agriculture and Food Security (CCAFS) has supported research in different parts of the world on how climate-smart technologies, practices and information can address the challenge of transitioning to climatesmart agriculture at a large scale under the new realities of climate change. The working paper critically examines how CCAFS researchers have conceptualized and practiced the scaling of climate-smart agriculture interventions. The review of CCAFS research is complemented by a discussion of some of the recent social science literature on scaling and closely related topics, such as (diffusion of) innovation and institutionalization. Although more recently the conceptual, methodological and practical challenges related to scaling of climate-smart agriculture have received more attention, there remains a need for the development of a more coherent theory of scaling informed by insights from sociology, political sciences and gender studies.